IMPLEMENTATION OF ORGANIC VEGETABLE PRODUCTION SYSTEM USING GOOD AGRICULTURE PRACTICES (GAP) AT PT. TANIKOTA - Anita Arga Putri Sitio; Dini Rochdiani (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
Good Agricultural Practice (GAP) has its own importance when applied in agribusiness with vegetable commodities because it is included in the requirements for supply to modern markets and maintains competition with global markets. The implementation of this GAP comprehensively certainly has its own difficulties in the implementation process in an agricultural area or area. The approach of the GAP is implemented intensively, although not entirely from each agricultural area. The implementation of this study is intended to further enhance the principles of agriculture and gain understanding related to the extent to which workers or business actors in the agricultural sector gain an understanding of the implementation of GAP and the extent to which business entities implement GAP implementation, the reference of which is included in the regulation of the ministry of agriculture number 48/Permentan. /OT.140/4/2009 and the obstacles experienced by business entities in implementing GAP. The research method used in this research is a case study with descriptive analysis. The results of the research show that there are things that are not in harmony and problems in the process of implementing this GAP, where the average percentage that has been able to be done is only 81.84%. The constraints experienced by business entities include: 1) Lack of understanding related to the concept of GAP 2) Logo Prima as a guarantee of food quality does not yet exist, 3) Product results are oriented to domestic needs. The implementation of organic vegetable production using GAP at PT Tanikota still has to be maximized, especially in seeding, planting.